Semi-Structured Interviews to Evaluate a BCMA Implementation Trouble Areas - Descalzo, Juan Marcos (2022)
Errors in medication administration involve risks to patient safety. 'Bar-Coding Medication Administration' is implemented to prevent these errors. Adoption by nurses is one of the main determinants of their effectiveness. The Hospital Italiano de Buenos Aires implemented BCMA 6 years ago, but its adoption rate still finds resistance in certain sectors. We conducted semi-structured interviews with nursing staff to explore the barriers to the use in low-usage wards and explore the current perceptions of nurses. While nurses recognised the safety and usefulness of the BCMA system, they reported many difficulties. The feedback obtained through this process was useful for the implementation team to plan future interventions, priorities and improvements on the system. The semi-structured interview methodology proved useful as a continuous monitoring strategy.